Identification of Bioactive Compounds in Meha Mudgara Rasa Using Gas Chromatography-Mass Spectrometry (GC-MS): Implications in Diabetic Neuropathy - Deshpande, Shailesh; Gandhi, Meha (Asian Journal of Biological and Life Sciences)
Introduction: Diabetic Neuropathy (DN) is a progressive and debilitating complication of Diabetes Mellitus (DM), primarily caused by chronic hyperglycaemia-induced microvascular damage to peripheral nerves. Despite existing conventional therapies, long-term effective management remains limited. Increasing attention is being directed toward Ayurvedic formulations for their potential role in managing Diabetes Mellitus (DM) and its complications. Materials and Methods: The classical Ayurvedic herbo-mineral formulation Meha Mudgara Rasa, traditionally used for DM management, was subjected to Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The formulation includes several therapeutic ingredients such as Dadima (Punica granatum), Triphala, Bilva (Aegle marmelos), and Gokshura (Tribulus terrestris), known for anti-diabetic and neuroprotective properties. The objective was to identify bioactive compounds potentially beneficial in the treatment of DN. Results: GC-MS profiling revealed the presence of multiple phytochemicals with documented pharmacological properties. These include compounds with anti-diabetic, antioxidant, anti-inflammatory, and neuroprotective effects, which may contribute to improved glycaemic control, reduced oxidative stress, and nerve tissue protection. Discussion: The identified phytoconstituents support the traditional use of Meha Mudgara Rasa in managing DM and DN. These findings suggest its potential as an adjuvant therapy. However, further pharmacological and clinical studies are necessary to confirm its safety and therapeutic efficacy in DN management. Conclusion: GC-MS analysis of Meha Mudgara Rasa highlights its rich phytochemical composition with potential therapeutic relevance in diabetic neuropathy. This study lays the groundwork for future research to validate its clinical utility and integrate traditional Ayurvedic wisdom with modern scientific approaches.
Keywords: Ayurveda; Diabetic Neuropathy; Neuroprotective; Herbo-mineral medicines.